Modulation of immortalizing properties of human papillomavirus type 16 E7 by p53 expression. - Crook, T (1991)
The E7 protein is one of the principle transforming proteins encoded by human papillomavirus type 16 (HPV16), a virus strongly associated with the development of cervical carcinoma. In the present study we show that cotransfection of wild-type human or murine p53 sequences with E7 and ras markedly reduces transformation in baby rat kidney cells, although no effect of p53 is seen on the ability of E7 to transform an established mouse line to anchorage independence. In contrast, expression of mutant p53 strongly potentiates the transforming function of E7 and confers marked growth factor independence to cells cotransformed by E7 and ras. These data suggest that E7 and p53 function in separate yet complementary biochemical pathways.